Twitter Storytelling as a New Literacy Practice - Holmes, Jeff (AoIR Selected Papers of Internet Research, 2013)
This paper analyzes the Twitter feed for the launch of Mass Effect 3 in order to explore the ways digital media reshape how we tell stories and share experiences. In particular, this feed highlights four important features of new media storytelling: the structure of the medium informs the crafted fictions of the story; these stories rely on both the “real” nature of the Twitter medium as well as the fictional context of the narrative world; the story exists within the “real world” of the reader by being enmeshed with their everyday stream of other writing and reading; and readers have opportunities to participate and actively engage with the story in new ways. Together, these features represent a new literacy and a new way of framing our understanding of storytelling.